Plant regeneration from immature seeds of Eugenia myrtifolia Sims. - Blando, Federica; Onlu, Seyma; Colella, Gianni; Konczak, Izabela (SPRINGER, 2013)
Eugenia myrtifolia Sims. is an evergreen shrub, native to temperate and tropical rainforests of Australia, which is becoming an important containerized ornamental plant in the US and Mediterranean nursery industries. To satisfy the growing market demands for this new ornamental plant, development of an accelerated propagation method is required. The goal of this study was to investigate the in vitro regeneration potential of E. myrtifolia Sims. seeds at different stages of development, towards establishment of an in vitro multiplication system. Maximum regeneration of adventitious shoots was achieved from immature seeds cultured in the dark on half-strength Murashige and Skoog (MS) macronutrients and full-strength MS micronutrients and vitamins (MS/2) medium supplemented with 2.5 mu M thidiazuron (TDZ). Induction of regeneration occurred after at least two successive subcultures on TDZ-enriched medium, followed by subcultures on expression medium (hormone free MS/2) or multiplication medium [MM; MS medium enriched with 4.4 M 6-benzyladenine and 0.05 M alpha-naphthaleneacetic acid], where complete development of shoots occurred. The regenerated shoots were excised and transferred again onto MM for micropropagation, where a proliferation rate of 1:4 was achieved, and finally the shoots were transferred to a hormone-free MS medium for rooting. Following ex vitro transplanting, acclimatization over a period of 15 d was sufficient to establish greenhouse plants. The regenerated plants grown in the field for more than 2 yr showed the same phenotype as that of mother plants. The adventitious regeneration and micropropagation carried out in this study can be used for a large-scale propagation and genetic engineering of E. myrtifolia Sims.
Keywords: Eugenia myrtifolia Sims.; Syzygium paniculatum Gaertn.; Ornamental plant; In vitro regeneration; Organogenesis; Immature seeds